The complete chloroplast genome of a gynodioecious deciduous orchid Satyrium ciliatum (Orchidaceae) female. Issue 2 (3rd July 2019) - Ma, Xiaokai; Lin, Han; Chen, Yanqiong; Lan, Siren; Ming, Ray
Abstract: The chloroplast (cp) genome sequence of a gynodioecious Satyrium ciliatum female type has been characterized using Illumina pair-end sequencing. The complete cp genome was 154, 418 bp in length, containing a large single copy region (LSC) of 83, 475 bp and a small single copy region (SSC) of 17, 513 bp, which were separated by a pair of 26, 715 bp inverted repeat regions (IRs). The genome contained 132 genes, with 113 unique genes, including 79 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. The overall GC content is 37.18% with the values of the LSC, SSC, and IR regions are 34.90%, 30.15%, and 43.06%, respectively. Phylogenetic analysis suggested that the S. ciliatum is close to Platanthera japonica (MG925368) in subfamily Orchidoideae.